Endovascular Treatment of Infrainguinal Chronic Total Occlusions Using the TruePath Device: Features, Handling, and 6-Month Outcomes. (April 2014) - Banerjee, Subhash; Sarode, Karan; Das, Thomas; Hadidi, Omar; Thomas, Rahul; Vinas, Ariel; Garg, Puja; Mohammad, Atif; Baig, Mirza S.; Shammas, Nicolas W.; Brilakis, Emmanouil S.
Purpose: To report experience with a recently approved peripheral chronic total occlusion (CTO) crossing device in the superficial femoral (SFA), popliteal, and below-the-knee (BTK) arteries. Methods: Thirteen patients (all men; mean age 68.6±7.9 years) from the XL PAD registry ( ClinicalTrials.gov identifier NCT01904851) were treated between April 2012 and August 2013 with the TruePath device after an unsuccessful guidewire crossing attempt. More than half of the patients had diabetes mellitus. Most lesions were TASC classification type C (n=5) or D (n=6), with mean lesion length 169.8±83.3 mm; 12 lesions were de novo and severely calcified. Procedure success was defined as successful revascularization of the CTO. Technical success was placement of a guidewire beyond the distal CTO cap into the true lumen without the need for a re-entry device. Results: All CTOs were successfully crossed using the TruePath, but 3 subintimal recanalizations required the use of a re-entry device (77% technical success). Eight lesions were stented, while the remaining were treated with balloon angioplasty and/or atherectomy. Average fluoroscopy time was 41.1±18.3 minutes, during which a mean 200.0±46.2 mL of iodinated contrast were used (radiation dose area product 211.2±202.6 Gy*cm 2 ). There were no periprocedural complications. Significant improvement was seen in the 6-month ankle-brachial index (p=0.018) and Rutherford class (p=0.019). The 6-month clinically indicated target vessel revascularization rate was 8%. Conclusion: TruePath facilitated successful crossing of infrainguinal CTOs following an unsuccessful guidewire recanalization, with significant improvement in symptoms and no complications.